Reconstituting the formation of hierarchically porous silica patterns using diatom biomolecules - Pawolski, Damian; Heintze, Christoph; Mey, Ingo; Steinem, Claudia; Kröger, Nils (Journal of structural biology, 2018)
The genetically-controlled formation of complex-shaped inorganic materials by living organisms is an intriguing phenomenon. It illustrates our incomplete understanding of biological morphogenesis and demonstrates the feasibility of ecologically benign routes for materials technology. Amorphous SiO2 (silica) is taxonomically the most widespread biomineral, with diatoms, a large group of single-celled microalgae, being the most prolific producers. Silica is the main component of diatom cell walls, which exhibit species-specific patterns of pores that are hierarchically arranged and endow the material with advantageous properties. Despite recent advances in characterizing diatom biomolecules involved in biosilica morphogenesis, the mechanism of this process has remained controversial. Here we describe the in vitro synthesis of diatom-like, porous silica patterns using organic components that were isolated from biosilica of the diatom Cyclotella cryptica. The synthesis relies on the synergism of soluble biomolecules (long-chain polyamines and proteins) with an insoluble nanopatterned organic matrix. Biochemical dissection of the process revealed that the long-chain polyamines rather than the proteins are essential for efficient in vitro synthesis of the hierarchically porous silica patterns. Our results support the organic matrix hypothesis for morphogenesis of diatom biosilica and introduce organic matrices from diatoms as a new tool for the synthesis of meso- to microporous inorganic materials.